Study the Effects of Dust and Sand Storms Attenuations on Satellites Link Margin over Libya - Sana Fadil, NassirAbuhamoud (Journal of Pure & Applied Sciences, 2020)
In this paper, the effect of dust and sand storm attenuation on the link margin of the satellite in geostationary orbit at X and Ku bands in the Space-to-Earth direction is studied for a satellite at 26°E longitude. A simulation model is used to predict the sand and dust storm attenuation and used to calculate thelink margin in six locations in Libya namely Benghazi, Tubruk, Tripoli, El-Kufra, Misrata and Sebha. The simulations assume 60 cm receive antenna diameter with 55% aperture efficiency. The downlink frequencies used in this study are 11.390 and 12.75 GHz for X- and Ku-bands respectively. The free space path loss, gases attenuations and scintillations fade dept are calculated for each band. Link margin, C/N and Es/No (dB) is computed at X and Ku bands. The results indicate that all sites achieve link margin above the threshold level (sensitivity)by 60 cm antenna diameter in all locations . The results show that the southern regions is the most affected by dust and sand storms attenuation and cases decreasing in link margin. In comparison to the Ku-band, the X-band was the more capable to maintain a good quality satellite link in dust and sand storm intensities.